Experimental and numerical study into the effects of passive flow disturbance on conversion and C7+ yield of the packed bed Fischer Tropsch reaction. (15th October 2019) - Wiryadinata, Steven; Jenkins, Bryan; Kornbluth, Kurt; Erickson, Paul
Highlights: Flow disturbance improves mass and heat transfer of the packed bed FT reaction. Flow disturbance extends the effective reactor length. The enhanced reactor shows higher conversion and C7+ yield relative to the baseline. Higher thermal conductivity and fluid velocity seem to drive performance increases. Abstract: This experimental and numerical study investigates the effect of flow field alteration via bluff body flow disturbers in the packed bed Fischer-Tropsch (FT) reaction, which is known to be limited by heat and mass transfer and chemical kinetics as prescribed by the reactor geometry, flow and temperature fields, and catalyst properties. Experiments were carried out using a 188 cm 3 reactor with 30.8 aspect (length-to-diameter) ratios loaded with 20% cobalt/Al2 O3 catalyst and controlled at 200 °C at the exterior wall. Numerical simulation was carried out in the commercial ANSYS Fluent package. Experimental results show that the bluff bodies increased the CO (carbon monoxide) conversion and C7+ yields (hydrocarbons with 7 carbon chains or longer) across the factorial design space by as much as 1.8× and 3.3× of the baseline values, respectively. Numerical simulations suggest that these increases can be attributed to higher thermal conductivities and local velocities for greater heat rejection and lower external mass transfer resistance, respectively. Results suggest that the use of internal flow disturbers in the packed bed had significant influence in lowering the heat and mass transfer resistances of the FT process, and can improve the cost-competitiveness of FT liquids production in the small scale.